The use of fourier series for image encryption - Genço?lu, Muharrem Tuincay (Institute of Electrical and Electronics Engineers Inc., 2018)
In this work, an image encryption algorithm was proposed using the Fourier Series. Then, we mentioned the method of mathematical analysis that should be done to strengthen this algorithm against the statistical attack. The development of this last algorithm has been left to professionals. © 2018 IEEE.
6th International Symposium on Digital Forensic and Security, ISDFS 2018 -- 22 March 2018 through 25 March 2018 -- Antalya -- 136277
Keywords: Algorithm; Correlation analysis; Image encryption